The impact of Th17 cells on transplant rejection and the induction of tolerance. - Heidt, S; Segundo, D; San, D; Chadha, R; Wood, K (2010)
PURPOSE OF REVIEW: This review aims to provide an overview of the latest evidence for the involvement of Th17 cells in the rejection of solid organ allografts. It will also consider the implications of the relationship between the differentiation pathways of Th17 and regulatory T cells (Tregs), as well as their plasticity in the context of transplantation tolerance. RECENT FINDINGS: In the absence of the Th1 lineage in vivo, Th17 cells are capable of rejecting cardiac allografts, showing the capacity of Th17 cells to cause allograft rejection, at least in experimental models. Th17 cells are relatively unsusceptible to suppression by Tregs, although this may be context dependent. Furthermore, addition of inflammatory signals to a Treg-inducing environment leads to Th17 development and established Tregs can be converted to Th17 cells under inflammatory conditions. SUMMARY: The capacity of Th17 cells to cause allograft rejection is becoming increasingly clear. However, the role and contribution of Th17 cells in allograft rejection in the presence of the full orchestra of T helper cells remains elusive. The apparent resistance of Th17 to be suppressed by Tregs may pose a hurdle for effective immunosuppression and tolerance inducing protocols. Furthermore, the close developmental pathways of Th17 and Tregs and the ability of Tregs to convert into Th17 cells in the presence of inflammatory signals may impede the establishment of specific unresponsiveness to donor alloantigens in vivo.